Social transition, socioeconomic status and self-rated health in China: evidence from a national cross-sectional survey (CGSS) - Gao, Yi; Zeng, Jing; Liao, Zangyi; Yang, Jing (Frontiers in Public Health, 2024)
Background Social transition is one of the multi-level mechanisms that influence health disparities. However, it has received less attention as one of the non-traditional social determinants of health. A few studies have examined China’s social transition and its impact on health inequality in self-rated health (SRH). Therefore, this study explores the impact of China’s market-oriented reforms—social transition and socioeconomic status (SES)—on residents’ SRH. Methods Using the cross-sectional data from the Chinese General Social Survey (CGSS) in 2017, we analyzed the effects of social transition and SES on the SRH of Chinese residents using the RIF (Recentered influence function) method. The RIF decomposition method investigated health differences among different populations and their determinants. Results Social transition and SES have significant positive effects on the SRH of Chinese residents. The correlation between SES and the SRH of Chinese residents is moderated by social transition, implying that social transition can weaken the correlation between SES and the SRH of Chinese residents. The impacts of SES and social transition on SRH vary across populations. Conclusion Promoting social transition and favoring disadvantaged groups with more resources are urgently needed to promote equitable health outcomes.